Virtual and Real Social Support Networks in Mental Health of Japanese HIV-Positive Men: Nationwide HIV/AIDS Web Research - Taisuke Togari; Yoji Inoue; Yosuke Takaku; Sakurako Abe; Rikuya Hosokawa; Takashi Itagaki; Sachiko Oki; Naoko Katakura; Chihiro Wakabayashi; Takashi Yajima (HIV/AIDS Research and Treatment-Open Journal, 2016)
Background: This cross-sectional study examined the effects of face-to-face (real) and virtual social support networks on the mental health status of Japanese HIV-positive males. Method: A nationwide online cross-sectional survey was conducted by HIV Futures Japan project from July 2013 to February 2014: 1,095 responses were obtained, and we analyzed those of 879 not females. Two subscales of the Hospital Anxiety and Depression Scale (HADS) were measured in depressive and anxiety tendencies. Results: The mean (SD) scores for depressive and anxiety tendencies were 8.1 (4.2) and 8.6 (4.8), respectively (the range was 0-21). Hierarchical regression analysis showed that virtual support networks did not display direct effects on depressive and anxiety tendency. “No one”, “only one” and “two to three” in the real-support network showed significant relations compared to “20 or more” (B=2.76, 1.86, 1.46, respectively. 95% CIs [1.35, 4.17], [0.28, 3.44], [0.10, 2.82], respectively) to the depressive tendency. With anxiety tendency, “no one”, “only one” and “two to three” in the real-support network showed a significant relation compared to “20 or more” (B=2.42, 2.04, 1.61, respectively. 95% CIs [0.83, 4.00], [0.27, 3.81], [0.08, 3.14], respectively). Conclusions: It is necessary to develop face-to-face social support systems to promote mental health among people living with HIV/AIDS.